1981
DOI: 10.1177/019459988108900522
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Breathing Disturbance Secondary to Nasal Obstruction

Abstract: The purpose of this study was to determine the effect of acute nasal obstruction on sleep and breathing in eight normal persons. The subjects were randomized into two groups. One night the subject was studied with the nose open and a second night with the nose obstructed. The electroencephalogram, electrocardiogram, inspiratory effort, nasal and oral airflow, and oxygen saturation were monitored. Sleep proved to be both subjectively and objectively disturbed. The subjects with the nose obstructed awoke more of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
5

Year Published

1985
1985
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(116 citation statements)
references
References 6 publications
1
110
0
5
Order By: Relevance
“…Poorly-controlled symptoms of allergic rhinitis may contribute to sleep loss or disturbance (94,96,(98)(99)(100)(101)(102)(103)(104). Moreover, sedation in patients with allergic rhinitis may be increased by using sedative treatments (105,106).…”
Section: Sleep Disturbancementioning
confidence: 99%
“…Poorly-controlled symptoms of allergic rhinitis may contribute to sleep loss or disturbance (94,96,(98)(99)(100)(101)(102)(103)(104). Moreover, sedation in patients with allergic rhinitis may be increased by using sedative treatments (105,106).…”
Section: Sleep Disturbancementioning
confidence: 99%
“…24,25 Studies in normal subjects demonstrate that nasal breathing increases ventilation by stimulating certain receptors in the nasal airway, and that occlusion of the nasal airway may produce decreased oropharyngeal patency. [26][27][28] Therefore, the nasal congestion associated with AR can limit maximal upper airway airflow and contribute to sleep disturbances. 29 Specific types of sleep disturbances or sleep-disordered breathing (SDB) related to increased airway resistance include snoring, upper airway resistance syndrome, and obstructive sleep apnoea syndrome.…”
Section: Mechanisms Of Nasal Congestion: Impact On Sleep Quality and mentioning
confidence: 99%
“…Various studies in the literature have indicated that nasal patency disorders should be treated as a potential risk factor for SDB development (24,25). For example, in a prospective study by Lofaso et al (26), it was stated that nasal patency disorders assessed on the basis of posterior rhinomanometry are independent risk factors for OSA development, although their impact was significantly weaker compared with the effect of obesity or facial bone abnormalities.…”
Section: Discussionmentioning
confidence: 99%